Swelling behavior of polymeric membranes to metalworking fluids. Issue 3 (12th September 2017) - Nguyen‐Tri, Phuong; Tuduri, Ludovic; Gauvin, Chantal; Triki, Ennouri; Vu‐Khanh, Toan
ABSTRACT: In some working places, such as metal manufacturing or automotive services, mechanical hazards commonly occur along with chemical hazards, particularly metalworking fluids (MWFs). The presence of these chemicals could modify the properties of gloves made from polymeric materials and thus reduce their protective properties against chemical contamination (solvent, MWFs) and mechanical risks (puncture and cutting). This work focused on determining the swelling characteristics and the resistance of six polymeric membranes which were exposed to seven industrial MWFs. We found that the swelling tests can be used to classify the potential of coating polymers in descending order of their resistance to MWFs: nitrile, polyurethane > poly(vinyl chloride), neoprene > butyl, latex. The analysis by multiple linear regression showed, for the first time, that the density or the viscosity‐gravity constant of the fluid and Hansen's solubility parameters of the polymers have a significant impact on the swelling of polymer. For the first time, two new multiple regression models have been proposed, to predict the swelling phenomena of polymers under various MWFs with an accuracy of ≈80%. The effect of temperature on mechanical properties and morphology of material was also examined. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2018, 135, 45717. Abstract :